2018
DOI: 10.21608/zjar.2018.49812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic, Mineral and Bio-Nitrogen Fertilization on Growth and Productivity of Some Snap Bean Cultivars Grown in Clay Soil

Abstract: This work was carried out during the two successive summer seasons of 2016 and 2017 in a Private Farm, Dondet Village, Meet Ghamr District, Dakhlia Governorate, Egypt to study the effect of various sources of nitrogen fertilization which equal 60 kg N/fad., on growth, yield and pod quality of snap bean cultivars (Paulista and Bronco) grown in clay soil under flood irrigation. The results showed that, fertilizing Paulista cultivar with 30 kg N as organic nitrogen (ON) + 30 kg N as MN/fad., (ammonium sulphate) +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In order to improve the production of snap bean, this can be accomplished by growing the cultivated area with the use of good cultivars for the best yield and good quality. Some researchers showed differences between snap bean cultivars for growth (Yunsheng et al, 2015;Hamaiel et al, 2016;Marzouk et al, 2016 andShafeek et al, 2017), yield and its components (Masa et al, 2017;Abdallah, 2018;Rahman et al, 2018;Saleh et al, 2018) and quality (Mandour, 2014;Beshir et al, 2015). They showed that there were significant differences between cultivars regarding plant growth, productivity and pod quality.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the production of snap bean, this can be accomplished by growing the cultivated area with the use of good cultivars for the best yield and good quality. Some researchers showed differences between snap bean cultivars for growth (Yunsheng et al, 2015;Hamaiel et al, 2016;Marzouk et al, 2016 andShafeek et al, 2017), yield and its components (Masa et al, 2017;Abdallah, 2018;Rahman et al, 2018;Saleh et al, 2018) and quality (Mandour, 2014;Beshir et al, 2015). They showed that there were significant differences between cultivars regarding plant growth, productivity and pod quality.…”
Section: Introductionmentioning
confidence: 99%